Indicators of the clinical And laboratory data Of patients With PostCovid sindrome In Uzbekistan (Retrospective And Prospective Analysis) - Makhfuza Rustamovna Bekchanova (Periodica Journal, 2024)
A comparative analysis of clinical, anamnestic and laboratory parameters of patients with COVID-19 was carried out using the method of retrospective and prospective examination. It was found that during treatment with antiviral drugs, a quarter of patients had changes of cytolysis markers. It was also shown that patients with comorbidity were more common in a prospective study.
Keywords: Covid-19; retrospective study; prospective analysis